Ford Beckman - Meg Webster - Sal Scarpitta - Robert Rauschenberg - Change Inc. Benefit - Token Gestures - Charles Clough : A Curatorial Project - Collins, Tricia; Milazzo, Richard (New York : Scott Hanson Gallery, 1990)
Beckman, Ford ; Bleckner, Ross ; Clough, Charles ; Ellis, Stephen ; Howey, Nicholas ; Kalina, Richard ; Lasker, Jonathan ; Polke, Sigmar ; Pozzi, Lucio ; Rauschenberg, Robert ; Reed, David ; Richter, Gerhard ; Scarpitta, Salvatore ; Schnabel, Julian ; Stella, Frank ; Stephan, Gary ; Suzuki, Taro ; Twombly, Cy ; Wasserman, Jeffrey ; Webster, Meg
cat. 7: Charles Clough, [16 p.]
Engels
A Curatorial Project by Collins & Milazzo, Scott Hanson Gallery, New York: Ford Beckman, January 6-27, 1990 ; Meg Webster : Drawings/Object - Projects Room, January 6-27, 1990 ; Sal Scarpitta in cooperation with Leo Castelli, February 3-24, 1990 ; Robert Rauschenberg: China Mix - Projects Room, February 3-24, 1990 ; Change Inc. Benefit, February 14, 1990 ; Token GEstures : A Painting Show, March 3-31, 1990 ; Charles Clough : Vistas and Vortices - Projects Room, March 3 -31, 1990
boek